Progress in drug delivery and diagnostic applications of carbon dots: a systematic review - Kaurav, Hemlata; Verma, Dhriti; Bansal, Amit; Kapoor, Deepak N.; Sheth, Sandeep (Frontiers in Chemistry, 2023)
Carbon dots (CDs), which have particle size of less than 10 nm, are carbon-based nanomaterials that are used in a wide range of applications in the area of novel drug delivery in cancer, ocular diseases, infectious diseases, and brain disorders. CDs are biocompatible, eco-friendly, easy to synthesize, and less toxic with excellent chemical inertness, which makes them very good nanocarrier system to deliver multi-functional drugs effectively. A huge number of researchers worldwide are working on CDs-based drug delivery systems to evaluate their versatility and efficacy in the field of pharmaceuticals. As a result, there is a tremendous increase in our understanding of the physicochemical properties, diagnostic and drug delivery aspects of CDs, which consequently has led us to design and develop CDs-based theranostic system for the treatment of multiple disorders. In this review, we aim to summarize the advances in application of CDs as nanocarrier including gene delivery, vaccine delivery and antiviral delivery, that has been carried out in the last 5 years.